Findings of 18F‐PI‐2620 tau PET imaging in patients with Alzheimer's disease and healthy controls in relation to the plasma P‐tau181 levels in a Japanese sample. Issue 4 (17th July 2022) - Bun, Shogyoku; Moriguchi, Sho; Tezuka, Toshiki; Sato, Yoshiaki; Takahata, Keisuke; Seki, Morinobu; Nakajima, Shinichiro; Yamamoto, Yasuharu; Sano, Yasunori; Suzuki, Natsumi; Morimoto, Ayaka; Ueda, Ryo; et al.
Abstract: Background: Alzheimer's disease (AD) is the most common cause of dementia worldwide. In AD, abnormal tau accumulates within neurons of the brain, facilitated by extracellular β‐amyloid deposition, leading to neurodegeneration, and eventually, cognitive impairment. As this process is thought to be irreversible, early identification of abnormal tau in the brain is crucial for the development of new therapeutic interventions. Aims: 18 F‐PI‐2620 is one of the second‐generation tau PET tracers with presumably less off‐target binding than its predecessors. Although a few clinical studies have recently reported the use of 18 F‐PI‐2620 tau PET in patients with AD, its applicability to AD is yet to be thoroughly examined. Methods: In the present pilot study, we performed 18 F‐PI‐2620 tau PET in seven cases of probable AD (AD group) and seven healthy controls (HC group). Standardized uptake value ratios (SUVR) in regions of interest (ROIs) in the medial temporal region and neocortex were compared between the AD and HC groups. Furthermore, correlations between regional SUVR and plasma p‐tau181 as well as cognitive test scores were also analyzed. Results: The uptake of 18 F‐PI‐2620 was distinctly increased in the AD group across all the ROIs. SUVR in all the target ROIs were significantly correlated with plasma p‐tau181 levels, as well as with MMSE and ADAS‐cog scores. Discussion & Conclusion: Our results add to accumulating evidence suggesting that 18 F‐PI‐2620 is a promising tau PET tracer that allows patients with AD to be distinguished from healthy controls, although a study with a larger sample size is warranted. Abstract : The present pilot study examined the ability of 18F‐PI‐2620 tau PET tracer to distinguish between healthy control and Alzheimer's disease, as well as correlations with plasma p‐tau181 and cognitive test results. Though the sample size was small, seven for each group, its SUVR in the target brain regions showed distinct differences between them and high correlations with plasma p‐tau181 and cognitive test results.